Reflections on student-university interactions for next generation learning - Wong, David (Emerald Group Publishing Limited, 2012)
This paper draws attention to the implications of an e-learning strategy – a strategy that is increasingly employed with greater intensity by many higher education institutions, by re-examining the value creation process from a service-dominant logic perspective. A model of student-faculty and student-student interactions using interactive Web 2.0 technologies in e-learning is offered and explained using literature from service-dominant logic research. This perspective fundamentally alters the mindset of higher education institutions that have traditionally devised strategies to deliver value through its products and services. The new focus provided by service-dominant logic is for higher education institutions to acknowledge that they can only facilitate the value creation process by fostering interactions, constructing learning activities that enable enriching learning experiences and creating structures to support these experiences. Key challenges for higher education institutions are discussed that include implications for exclusion marketing, perceived value for money, and policy issues. Originality/value – This paper provides a fresh perspective, and a new line of thinking with regard to how value is co-created by both faculty and students through a set of experiences within student-faculty and student-student interactions. It therefore potentially directs a new path of research in the area.